2002
DOI: 10.1007/s00266-002-1495-y
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Ipsilateral Versus Contralateral Pedicle and Vertical Versus Horizontal Flap Inset Models in TRAM Flap Breast Reconstruction: The Aesthetic Outcome

Abstract: The use of an ipsilateral or a contralateral rectus abdominis muscle as a pedicle and comparison of their advantages and disadvantages in TRAM flap breast reconstruction have been reported in the literature. In our clinical experience with 22 pedicled TRAM flap breast reconstructions, the use of either an ipsilateral or contralateral pedicle was found to be equivocal regarding the flap viability and the aesthetic outcome. Thus, it seems better to decide their use according to the needs of an individual patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…However, in cases of ptotic breasts, contralateral TRAM flaps in a vertical position were preferred to better fill the lower pole. Ozkan et al 4 also reported using this technique in small breasts 1 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in cases of ptotic breasts, contralateral TRAM flaps in a vertical position were preferred to better fill the lower pole. Ozkan et al 4 also reported using this technique in small breasts 1 .…”
Section: Discussionmentioning
confidence: 96%
“…Lower tension on the pedicle reduces venous resistance and improves flap perfusion. Moreover, it diminishes the neces sity for extensive flap dissection or costal cartilage removal, maneuvers that can be used with the contralateral TRAM flap to reduce tension [1][2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publications describe various orientations. 17,18 In our model, the flap is rotated 180 degrees from its donor position in patients with large chest widths and in those who require exaggerated ptosis. The flap is rotated 90 degrees in narrow-chested patients and in those who will benefit from superior fullness.…”
Section: Part Ii: Contour the Flapmentioning
confidence: 99%
“…There are reports indicating differences in early and long-term outcome of these two techniques [9] . Some authors reported similar safety of both techniques [10] while others favored one pedicle TRAM technique over the other one [8,9] .…”
Section: Introductionmentioning
confidence: 98%